Use of GPS and accelerometers in sports and physical activity - Leger, L.; Bekraoui, N. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
INTRODUCTION. The quantitative and qualitative measure of physical activity, motion and gesture in task and time-motion analyses of day-to-day activities and sports and fitness testing as well, are important for fitness trainers, health practitioners and epidemiologists. Visual and video observations, logbooks and recall questionnaires have been used for a long time while GPS and accelerometers are more recent in that field. QUANTITATIVE METHODS. However quantitative methods such as GPS and accelerometers are not oriented toward qualitative measures. Forward and backward displacements could not be differentiated; specific gestures such as kicking, throwing could not be identified nor interaction with partners or opponents. Thus they could not replace visual methods but complement those particularly for rapid computation of quantitative measures of acceleration, speed, displacement, orientation and even position. VALIDATION STUDIES. The general principles behind GPS and accelerometers will be described along with main advantages and disadvantages. Of course, the technical characteristics of available models (particularly the sampling frequency, memory...) affect those. Focus is made on commercially available and affordable models (Garmin E-Trek & MAP-76A GPS (1Hz) RT3 accelerometer (1Hz).). Some validity results are based on the utilization of two common running multistage field tests as the criterion methods. Both tests use an audio signal to set the speed between equidistant 50-m markers along a 400-m track or at each end of a 20-m shuttle course. Frequency of sound signal is increased at each stage to yield regular mean speed increments. In the forward running track test, speed is maintained constant during the stage while there are accelerations and decelerations with 180 degree direction changes in the shuttle test. With common 1 Hz sampling rate of commercial devices, the GPS is better than the accelerometer to indicate accurate changes in speed, displacement, direction and position. However, none of the 1-Hz sampling rate device is good enough to detect important and short (< 1 s) change of speed). New high sampling frequency devices such as the Garmin GPS 18 (5 Hz) or the Antaris U-Blox (4Hz) improve greatly the accuracy of the measures when rapid changes are occurring... SPORT APPLICATION. The rest of the presentation will focus in reviewing applications of these tools in sport studies such as football, cycling or running.